Edukasi Perencanaan Tata Kelola Ruang Terbuka Biru untuk Mengatasi Bencana Banjir Di Wilayah Desa Klambir V Kebun, Kecamatan Hamparan Perak Deli Serdang - Lubis, Ruri Prihatini (Jurnal Masyarakat Indonesia (Jumas), 2025)
The flood issues in the Hamparan Perak area, Deli Serdang that happened every rainy season is a very anxious issue in the community. Education on Blue Open Space Management Planning to Overcome Flood Disasters in the Klambir V Kebun Village Area, Hamparan Perak District, Deli Serdang needs to be carried out routinely so that the community understands the management of blue open spaces, their benefits and how to implement them. The main objective of this activity is to provide education to residents so that they can prevent flooding. Participants in this education are the community in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang. The activity begins with an introduction to the location conditions and an explanation of the benefits of blue open spaces. The methods used are presentations and discussions.